The effect of autologous platelet-rich plasma (PRP) as a stand-alone treatment, In improving the thickness of the uterine lining receptivity and nesting - بايزيد, لطيفة; حسن صالح; ثورة نعيسه (Latakia University Journal -Medical Sciences Series, 2024)
Objective: To evaluate the effectiveness of platelet rich plasma in treating women with thin endometrial thickness. Methods: Twenty-seven cases participated in the research. The patients who participated in this study were referred to the Department of Obstetrics and Gynecology at Tishreen University Hospital in Lattakia, Syria. In Lattakia, between October 2022-May 2023 AD., with a history of primary or secondary infertility, having a thin uterine lining less than or equal to 7 mm.The age group included in the study ranged from 27 years to 45 years. The primary outcomes studied were the outcome of endometrial thickness, pregnancy rate and abortion rate. Results: Pregnancy Outcome Study: Number of participants: 27 patients: The average endometrial thickness After the second injection, 8.55 ± 3.5 mm The number of women who achieved a chemical pregnancy reached 4 4/27 participants, at a rate of (14.8%). The number of clinical pregnancies 1, 1/27, with a rate of (3.7%) The number of early abortions is 3, 3/27, at a rate of (11.1%). The number of live births 1, 1/27, at a rate of (3.7%) The PRP injection was shown to be a significant fact related to the day of injection, when the first PRP infusion was performed on the 10th day, and the second infusion on the 12th day of the menstrual cycle. We note that: The number of abortions was 3 cases, the rate (75%) The number of live births was 1, the rate (25%). Conclusion: Platelet Rich Plasma (PRP) infusion has been shown to be an effective treatment for thin endometrium.and it is preferable to use it with hormonal therapy to increase the rate of live births.